Development of genomic tools for verification of hybrids and selfed progenies in cassava (Manihot esculenta) - Otti, G.; Fakoya, A.; Andrew, I.; Gedil, Melaku A (Academic Journals, 2011)
Cross contamination arising from random natural processes and breeding errors is one of the prominent challenges to breeding in many crops including cassava (Manihot esculenta). This study attempts to identify molecular marker tools suitable for verifying the genetic purity of putative progenies of populations of cassava. It also proposes a rapid, high-throughput genomic DNA extraction protocol which is a modification of an existing extraction protocol adapted to the pace required for the DNA-based verification of often large population sizes. Three polymorphic simple sequence repeat (SSR) markers were selected from a total of 125 and used for genotyping three populations. The petiole color trait was also used to verify TMS 96/1089A X TME117 where the pink color of the male parent was dominant over the female’s green color. The pace of genomic analysis of populations used in the study was enhanced using a modified , quicker DNA isolation protocol which slashed extraction time by 60%. SSRY153 identified six Limited Access progenies in the selfed line, 1M18. Segregation patterns of In combination, both markers identified 2 selfed individuals out of a total of 207. NS890 identified two Limited Access hprogenies resulting from selfing in the female parent of the cross TMS 30001 X TMS 96/1089A, out of a total of 93, The principles described for verification using each of the SSR markers applied in this study can be extended to other SSR markers with corresponding nature of polymorphism in any population of the crop. Increased attention would go to the development of more efficient markers such as single nucleotide polymorphisms (SNPs) and other gene-based markers using new and advanced genomics techniques for routine integration of such quality control step in the breeding scheme.